Outliers: the story of success (Little, Brown and Co. Large Print, Blackstone Audio, Inc., Hachette Audio, Little, Brown and Company, Findaway World, Little, Brown and Co, 2008)
The best-selling author of Blink identifies the qualities of successful people, posing theories about the cultural, family, and idiosyncratic factors that shape high achievers, in a resource that covers such topics as the secrets of software billionaires, why certain cultures are associated with better academic performance, and why the Beatles earned their fame.
The Roseto mystery , The Matthew effect (Matthew 25:29) , The 10,000 hour rule (Hamburg) , The trouble with geniuses & IQ , The lessons of Joe Flom , Harlan, Kentucky , The ethnic theory of plane crashes , Rice paddies and math tests , Marita's bargain (KIPP) , A Jamaican story.

You are a badass (Tantor Media, Inc., Hachette Audio, Hachette Book Group, Tantor Media, Running Press, Findaway World, LLC, Tantor Audio, 2017)
"You are a Badass has inspired millions of people all over the world - including the snarkiest of skeptics - to embrace their awesomeness, give fear the heave-ho, and start kicking some serious ass. Now it's dressed up in a new hardcover edition, but it's the same 'classic' book that helps you create a life you love via hilariously inspiring stories, sage advice, easy exercises, and the occasional swear word."--Page [4] of cover.
Introduction , How you got this way. My subconscious made me do it , The G-word , Present as a pigeon , The big snooze , Self-perception is a zoo , How to embrace your inner badass. Love the one you is , I know you are but what am I? , What are you doing here? , Loincloth man , How to tap into the motherlode. Meditation 101 , Your brain is your bitch , Lead with your crotch , Give and let give , Gratitude: the gateway drug to awesomeness , Forgive or fester , Loosen your bone, Wilma , How to get over your B.S. already. It's so easy once you figure out it isn't hard , Procrastination, perfection, and a Polish beer garden , The drama of overwhelm , Fear is for suckers , Millions of mirrors , The sweet life , How to kick some ass. The almighty decision , Money, your new best friend , Remember to surrender , Doing vs. spewing , Beam me up, Scotty.

The view from the cheap seats: selected nonfiction (HarperCollins, HarperAudio, HarperLuxe, an imprint of HarperCollins Publishers, William Morrow, an imprint of HarperCollins Publishers, HarperCollins Publishers, 2016)
"An enthralling collection of nonfiction essays on a myriad of topics--from art and artists to dreams, myths, and memories--observed in #1 New York Times bestselling author Neil Gaiman's probing, amusing, and distinctive style. An inquisitive observer, thoughtful commentator, and assiduous craftsman, Neil Gaiman has long been celebrated for the sharp intellect and startling imagination that informs his bestselling fiction. Now, The View from the Cheap Seats brings together for the first time ever more than sixty pieces of his outstanding nonfiction. Analytical yet playful, erudite yet accessible, this cornucopia explores a broad range of interests and topics, including (but not limited to): authors past and present; music; storytelling; comics; bookshops; travel; fairy tales; America; inspiration; libraries; ghosts; and the title piece, at turns touching and self-deprecating, which recounts the author's experiences at the 2010 Academy Awards in Hollywood. Insightful, incisive, witty, and wise, The View from the Cheap Seats explores the issues and subjects that matter most to Neil Gaiman--offering a glimpse into the head and heart of one of the most acclaimed, beloved, and influential artists of our time."-- Amazon.com.
Some things I believe. Why our future depends on libraries, reading and daydreaming : the Reading Agency Lecture, 2013 ; Telling lies for a living...and why we do it : the Newbery Medal Speech, 2009 ; Four bookshops ; Three authors : on Lewis, Tolkien and Chesterton; the MythCon 35 Guest of Honor Speech ; The pornography of genre, or the genre of pornography ; Ghosts in the machines : some Hallowe'en thoughts ; Some reflections on myth (with several digressions onto gardening, comics and fairy tales) ; How dare you : on America, and writing about it ; All books have genders ; the PEN Awards and Charlie Hebdo ; What the [very bad swearword] is a children's book, anyway? The Zena Sutherland Lecture , Some people I have known. These are not our faces ; Reflections : on Diana Wynne Jones ; Terry Pratchett : an appreciation ; On Dave McKean ; How to read Gene Wolfe ; Remembering Douglas Adams ; Harlan Ellison : The Beast That Shouted Love at the Heart of the World ; Banging the drum for Harlan Ellison ; On Stephen King, for the Sunday Times ; Geoff Notkin : meteorite man ; About Kim Newman, with notes on the creation and eventual dissolution of the Peace and Love Corporation ; Gumshoe : a book review ; SIMCITY ; Six to six , Introductions and musings : science fiction. Fritz Leiber : the short stories ; Hothouse ; Ray Bradbury, Fahrenheit 451 and what science fiction is and does ; Of time, and Gully Foyle : Alfred Bester and The Stars My Destination ; Samuel R. Delany and The Einstein Intersection ; On the fortieth anniversary of the Nebula Awards : a speech, 2005 , Films and movies and me. The Bride of Frankenstein ; MirrorMask : an introduction ; MirrrorMask : a Sundance diary ; The nature of the infection : some thoughts on Doctor Who ; On comics and films : 2006 , On comics and some of the people who make them. Good comics and tulips : a speech ; A speech to professionals contemplating alternative employment, given at PROCON, April 1997 ; "But what has that to do with Bacchus?" Eddie Campbell and Deadface ; Confessions : on Astro City and Kurt Busiek ; Batman : Cover to Cover ; Bone : an introduction, and some subsequent thoughts ; Jack Kirby : king of comics ; The Simon and Kirby Superheroes ; The spirit of seventy-five ; The Best of the Spirit ; Will Eisner : New York stories ; The keynote speech for the 2003 Eisner Awards ; 2004 Harvey Awards speech ; The Best American Comics, 2010 , Introductions and contradictions. Some strangeness in the proportion : the exquisite beauties of Edgar Allan Poe ; On The New Annnotated Dracula ; Rudyard Kipling's Tales of Horror and Fantasy ; From the days of future past : The Country of the Blind and Other Stories, by H.G. Wells ; Business as usual, during alterations : Information Doesn't Want to Be Free, by Cory Doctorow ; The mystery of G.K. Chesterton's Father Brown ; Concerning dreams and nightmares : the dream stories of H.P. Lovecraft ; On The 13 Clocks by James Thurber ; Votan and Other Novels by John James ; On Viriconium : some notes toward an introduction ; So Long, and Thanks for All the Fish : an introduction ; Dogsbody by Diana Wynne Jones ; Voice of the Fire by Alan Moore ; Art and Artifice by Jim Steinmeyer ; The Moth : an introduction , Music and the people who make it. Hi, by the way : Tori Amos ; Curious wine : Tori Amos II ; Flood : Twenty-fifth Anniversary Edition, They Might Be Giants ; Lou Reed, in memoriam : "The Soundrack to My Life" ; Waiting for the man : Lou Reed ; Afterword afterword : Evelyn Evelyn ; Who Killed Amanda Palmer , On 'Stardust' and fairy tales. Once upon a time ; Several things about Charles Vess ; The King of Elfland's daughter, Lord Dunsany ; Lud-in-the-Mist ; The thing of it is : Jonathan Strange and Mr. Norrell ; On Richard Dadd's The Fairy-Feller's Master-Stroke , Make good art. Make good art , The view from the cheap seats : real things. The view from the cheap seats ; A wilderness of mirrors ; The Dresden dolls : Hallowe'en 2010 ; Eight views of Mount Fuji : Beloved Demons and Anthony Martignetti ; So many ways to die in Syria now : May 2014 ; A Slip of the Keyboard : Terry Pratchett.

Nickel and dimed: on (not) getting by in America (Recorded Books, Inc., Picador, Metropolitan Books, Recorded Books, Picador, a Metropolitan book/Henry Holt and Company, Henry Holt and Co., 2004)
Millions of Americans work full-time, year-round, for poverty-level wages. In 1998, the author decided to join them. She was inspired in part by the rhetoric surrounding welfare reform, which promised that a job, any job, can be the ticket to a better life. But how does anyone survive, let alone prosper, on $6 an hour? To find out, she left her home, took the cheapest lodgings she could find, and accepted whatever jobs she was offered. Moving from Florida to Maine to Minnesota, she worked as a waitress, a hotel maid, a cleaning woman, a nursing home aide, and a Wal-Mart sales clerk. She lived in trailer parks and crumbling residential motels. Very quickly, she discovered that no job is truly "unskilled," and that even the lowliest occupations require exhausting mental and muscular effort. She also learned that one job is not enough; you need at least two if you intend to live indoors. This work reveals low-rent America in all its tenacity, anxiety, and surprising generosity, a land of Big Boxes, fast food, and a thousand desperate strategems for survival. Read it for the author's perspective and for a rare view of how "prosperity" looks from the bottom. You will never see anything, from a motel bathroom to a restaurant meal, quite the same way again. In her new afterword she explains why, ten years on in America this book is more relevant than ever.
Getting ready , Serving in Florida , Scrubbing in Maine , Selling in Minnesota , Evaluation , Afterword : Nickel and dimed , Reader's Guide.

So you want to be president? (Caldecott Medal Winner, ,, 2002)
This new version of the Caldecott-winning classic by illustrator David Small and author Judith St. George is updated with current facts and new illustrations to include our forty-fourth president, Barack H. Obama. Hilariously illustrated by Small, this celebration by St. George shows us the foibles, quirks and humanity of forty-four men who have risen to one of the most powerful positions in the world.

Four hundred souls: a community history of African America, 1619-2019 (One World, Random House Large Print, Books on Tape, Random House Audio, 2021)
"A "choral history" of African Americans covering 400 years of history in the voices of 80 writers, edited by the bestselling, National Book Award-winning historian Ibram X. Kendi and Keisha N. Blain. Last year marked the four hundredth anniversary of the first African presence in the Americas--and also launched the Four Hundred Souls project, spearheaded by Ibram X. Kendi, director of the Antiracism Institute of American University, and Keisha Blain, editor of The North Star. They've gathered together eighty black writers from all disciplines -- historians and artists, journalists and novelists--each of whom has contributed an entry about one five-year period to create a dynamic multivoiced single-volume history of black people in America"--
A community of souls : an introduction / by Ibram X. Kendi --, Part one. 1619-1624 : arrival / by Nikole Hannah-Jones ; 1624-1629 : Africa / by Molefi Kete Asante ; 1629-1634 : whipped for lying with a Black woman / by Ijeoma Oluo ; 1634-1639 : tobacco / by Damaris B. Hill ; 1639-1644 : Black women's labor / by Brenda E. Stevenson ; 1644-1649 : Anthony Johnson, colony of Virginia / by Maurice Carlos Ruffin ; 1649-1654 : the Black family / by Heather Andrea Williams ; 1654-1659 : unfree labor / by Nakia D. Parker ; Poem : "upon arrival" by Jericho Brown --, Part two. 1659-1664 : Elizabeth Keye / by Jennifer L. Morgan ; 1664-1669 : the Virginia law on baptism / by Jemar Tisby ; 1669-1674 : the royal African company / by David A. Love ; 1674-1679 : Bacon's rebellion / by Heather C. McGhee ; 1679-1684 : the Virginia law that forbade bearing arms; or the Virginia law that forbade armed self-defense / by Kellie Carter Jackson ; 1684-1689 : the code noir / by Laurence Ralph ; 1689-1694 : the Germantown petition against slavery / by Christopher J. Lebron ; 1694-1699 : the middle passage / by Mary E. Hicks ; Poem : "Mama, where you keep your gun?" / by Phillip B. Williams --, Part three. 1699-1704 : the selling of Joseph / by Brandon R. Byrd ; 1704-1709 : the Virginia slave codes / by Kai Wright ; 1709-1714 : the revolt in New York / by Herb Boyd ; 1714-1719 : the slave market / by Sasha Turner ; 1719-1724 : maroons and marronage / by Sylviane A. Diouf ; 1724-1729 : the spirituals / by Corey D. B. Walker ; 1729-1734 : African identities / by Walter C. Rucker ; 1734-1739 : from Fort Mose to soul city / by Brentin Mock ; Poem : "before revolution" / by Morgan Parker --, Part four. 1739-1744 : the Stono rebellion / by Wesley Lowery ; 1744-1749 : Lucy Terry Prince / by Nafissa Thompson-Spires ; 1749-1754 : race and the enlightenment / by Dorothy E. Roberts ; 1754-1759 : Blackness and indigeneity / by Kyle T. Mays ; 1759-1764 : one Black boy : the Great Lakes and the Midwest / by Tiya Miles ; 1764-1769 : Phillis Wheatley / by Alexis Pauline Gumbs ; 1769-1774 : David George / by William J. Barber II ; 1774-1779 : the American revolution / by Martha S. Jones ; Poem : "not without some instances of uncommon cruelty" / by Justin Phillip Reed --, Part five. 1779-1784 : Savannah Georgia / by Daina Ramey Berry ; 1784-1789 : the U.S. Constitution / by Donna Brazile ; 1789-1794 : Sally Hemings / by Annette Gordon-Reed ; 1794-1799 : the fugitive slave act / by Deirdre Copper Owens ; 1799-1804 : higher education / by Craig Steven Wilder ; 1804-1809 : cotton / by Kiese Laymon ; 1809-1814 : the Lousiana rebellion / by Clint Smith ; 1814-1819 : queer sexuality / by Raquel Willis ; Poem : "remembering the Albany 3" / by Ishmael Reed --, Part six. 1819-1824 : Denmark Vesey / by Robert Jones, Jr. ; 1824-1829 : Freedom's Journal / by Pamela Newkirk ; 1829-1834 : Maria Stewart / by Kathryn Sophia Belle ; 1834-1839 : the national Negro conventions / by Eugene Scott ; 1839-1844 : racial passing / by Allyson Hobbs ; 1844-1849 : James McCune Smith, M.D. / by Harriet A. Washington ; 1849-1854 : Oregon / by Mitchell S. Jackson ; 1854-1859 : Dred Scott / by John A. Powell ; Poem : "compromise" / by Donika Kelly --, Part seven. 1859-1864 : Frederick Douglass / by Adam Serwer ; 1864-1869 : the Civil War / by Jamelle Bouie ; 1869-1874 : reconstruction / by Michael Harriot ; 1874-1879 : Atlanta / by Tera W. Hunter ; 1879-1884 : John Wayne Niles / by William A. Darity, Jr. ; 1884-1889 : Philadelphia / by Kali Nicole Gross ; 1889-1894 : lynching / by Crystal N. Feimster ; 1894-1899 : Plessy v. Ferguson / by Blair L. M. Kelley ; Poem : "John Wayne Niles ... . --, . .- -.- ... / - , - Ermias Joseph Asghedom" by Mahogany L. Browne ; Part eight. 1899-1904 : Booker T. Washington /, by Derrick Alridge ; 1904-1909 : Jack Johnson / by Howard Bryant ; 1909-1914 : the Black public intellectual / by Beverly Guy-Sheftall ; 1914-1919 : the great migration / by Isabel Wilkerson ; 1919-1924 : red summer / by Michelle Duster ; 1924-1929 : the Harlem Renaissance / by Farah Jasmine Griffin ; 1929-1934 : the Great Depression / by Robin D. G. Kelley ; 1934-1939 : Zora Neale Hurston / by Bernice L. McFadden ; Poem : "coiled and unleashed" by Patricia Smith --, Part nine. 1939-1944 : the Black soldier / by Chad Williams ; 1944-1949 : the Black left / by Russell Rickford ; 1949-1954 : the road to Brown v. Board of Education / by Sherrilyn Ifill ; 1954-1959 : Black arts / by Imani Perry ; 1959-1964 : the Civil Rights Movement / by Charles E. Cobb, Jr. ; 1964-1969 : Black power / by Peniel Joseph ; 1969-1974 : property / by Keeanga-Yamahtta Taylor ; 1974-1979 : Combahee river collective / by Barbara Smith ; Poem : "and the record repeats" / by Chet'la Sebree --, Part ten. 1979-1984 : the war on drugs / by James Forman, Jr. ; 1984-1989 : the hip-hop generation / by Bakari Kitwana ; 1989-1994 : Anita Hill / by Salamishah Tillet ; 1994-1999 : the crime bill ; by Angela Y. Davis ; 1999-2004 : the Black immigrant / by Esther Armah ; 2004-2009 : Hurricane Katrina / by Deborah Douglas ; 2009-2014 : the Shelby ruling / by Karine Jean-Pierre ; 2014-2019 : Black Lives Matter / by Alicia Garza ; Poem : American Abecedarian" / by Joseph Bennett --, Conclusion : our ancestor's wildest dreams / by Keisha N. Blain.

Until the end of time: mind, matter, and our search for meaning in an evolving universe (Random House Large Print, Vintage Books, Alfred A. Knopf, Books on Tape, Random House Audio, 2021)
"From the world-renowned physicist, co-founder of the World Science Festival, and best-selling author of The Elegant Universe comes this utterly captivating exploration of deep time and humanity's search for purpose. Brian Greene takes readers on a breathtaking journey from the big bang to the end of time and invites us to ponder meaning in the face of this unimaginable expanse. He shows us how, from its original orderly state the universe has been moving inexorably toward chaos, and, still, remarkable structures have continually formed: the planets, stars, and galaxies that provide islands in a sea of disorder; biochemical mechanisms, including mutation and selection, animate life; neurons, information, and thought developed into complex consciousness which in turn gave rise to cultures and their timeless myths and creativity. And he describes, as well, how, in the deep reaches of the future, the nature of the universe will threaten the existence of matter itself. Through a series of nested stories Greene provides us with a clearer sense of how we came to be, a finer picture of where we are now, and a firmer understanding of where we are headed. Taken together, it is a completely new perspective on our place in the universe and on what it means to be human." --
The lure of eternity : beginnings, endings, and beyond , The language of time : past, future, and change , Origins and entropy : from creation to structure , Information and vitality : from structure to life , Particles and consciousness : from life to mind , Language and story : from mind to imagination , Brains and belief : from imagination to the sacred , Instinct and creativity : from the sacred to the sublime , Duration and impermanence : from the sublime to the final thought , The twilight of time : quanta, probability, and eternity , The nobility of being : mind, matter, and meaning.

Guts (Guts, ,, 2019)
"Raina wakes up one night with a terrible upset stomach. Her mom has one, too, so it's probably just a bug. Raina eventually returns to school, where she's dealing with the usual highs and lows: friends, not-friends, and classmates who think the school year is just one long gross-out session. It soon becomes clear that Raina's tummy trouble isn't going away... and it coincides with her worries about food, school, and changing friendships. What's going on?" --

African icons: ten people who shaped history (Hachette Audio, Workman Publishing Co. Inc, Workman Publishing Company, Algonquin Young Readers, 2021)
"Full-color portraits illustrate the stories of ten people--rulers, educators, inventors, scholars, and explorers--who helped shape the African continent and the world from ancient times through the tumultuous sixteenth century"--
Introduction: When Africa Fueled the World , The Sahara Yawns: Menes: Creator of Dynasties , Merneith: A Queen Erased , The Dawn of Egypt: Imhotep: From Peasant to God , Metal Bonds , Nature as Character: Aesop: The Wisest Man in the Ancient World , Across the Waves: Hannibal Barca: Unparalleled Military Strategist , Terence: North African Playwright , Amanirenas: Warrior, Diplomat, Queen , Where Few Dared to Tread: Tin Hinan: Founding a City on the Dunes , Across the Golden Sand: Mansa Musa: The Richest Man of All Time , The Catalan Atlas , The Power of the Griot , Libraries in the Sand , The Winds Change: Queen Idia: Kingmaker , Culture Lost , Author's note , Source notes , Bibliography , Index , Designer's Note.

Trains (Machines at work, ,, 2008)
Explains what different parts make up a train, that trains travel on special railroad tracks, and what trains are used to transport.
On the job , Climb aboard! , Up close , Glossary.

Shark attack! (DK super readers, ,, 1998)
"Sharks-savage killers or fascinating sea creatures? Make reading your superpower with DK's beautiful, leveled nonfiction. Use your reading superpowers to learn all about sharks, both feared and fascinating-a high-quality, fun, nonfiction reader-carefully leveled to help children progress"--
Shark attack! , Shark attacks , the facts , Sharks and safety , Sharks up close , Sharks under attack.

Words are not for hurting (Best Behavior, ,, 2017)
Encourages toddlers and preschoolers to express themselves using helpful, not hurtful, words. Includes a note for parents and caregivers on language development.

Vietnam (Cultures of the world, ,, 1994)
"The history of Vietnam is complicated and filled with conflict, and that history has impacted the nation's culture in major ways. Readers explore the relationship between Vietnam's history, geography, and culture in this thoroughly updated look at the Southeast Asian nation. With chapters highlighting economics, arts, religion, language, and the lifestyles of the Vietnamese people, readers are given a comprehensive overview of Vietnam that is enhanced by vibrant full-color photographs. Fact boxes and maps provide additional information, sidebars spotlight global citizens in Vietnam, and recipes allow readers to explore Vietnamese culture in a hands-on and creative way"--
Introduction , Geography , History , Government , Economy , Vietnamese , Lifestyle , Religion , Language , Arts , Leisure , Festivals , Food.

Life's edge: the search for what it means to be alive (Dutton, an imprint of Penguin Random House LLC, Penguin Publishing Group, Books on Tape, 2021)
"What is life? The power seems obvious until you try to seriously answer it. Zimmer journeys through experiments that have attempted to recreate life; shows how coronaviruses have altered the course of history; and even tries his own had at evolving life in a test tube... with unnerving results." --
Introduction: The borderland , The quickening. The way the spirit comes to the bones ; Death is resisted , The hallmarks. Dinner ; Decisive matter ; Preserving constant the conditions of life ; Copy/Paste ; Darwin's lung , A series of dark questions. This astonishing multiplication ; Irritations ; The sect ; This mud was actually alive ; A play of water ; Scripts , Return to the borderland. Half life ; Data needed for a blueprint ; No obvious bushes ; Four blue droplets.

Honeybee: the busy life of Apis mellifera (Dreamscape Media, Holiday House, Neal Porter Books, an imprint of Holiday House, 2022)
"Describes the life cycle of the hard-working honeybee." --

All the living and the dead: from embalmers to executioners, an exploration of the people who have made death their life's work (St. Martin's Press, St. Martin's Publishing Group, Macmillan Audio, 2022)
"A deeply compelling exploration of the death industry and the people-morticians, detectives, crime scene cleaners, embalmers, executioners-who work in it and what led them there. We are surrounded by death. It is in our news, our nursery rhymes, our true-crime podcasts. Yet from a young age, we are told that death is something to be feared. How are we supposed to know what we're so afraid of, when we are never given the chance to look? Fueled by a childhood fascination with death, journalist Hayley Campbell searches for answers in the people who make a living by working with the dead. Along the way, she encounters mass fatality investigators, embalmers, and a former executioner who is responsible for ending sixty-two lives. She meets gravediggers who have already dug their own graves, visits a cryonics facility in Michigan, goes for late-night Chinese with a homicide detective, and questions a man whose job it is to make crime scenes disappear. Through Campbell's incisive and candid interviews with these people who see death every day, she asks: Why would someone choose this kind of life? Does it change you as a person? And are we missing something vital by letting death remain hidden? A dazzling work of cultural criticism, All the Living and the Dead weaves together reportage with memoir, history, and philosophy, to offer readers a fascinating look into the psychology of Western death"--
The edge of mortality: Funeral director , The gift: Director of anatomical services , Click your fingers and they turn to stone: Death mask sculptor , Limbo: Disaster victim identification , The horror: Crime scene cleaner , Dining with the executioner: Executioner , None of this is forever: Embalmer , Love and terror: Anatomical pathology technologist , Tough mother: Bereavement midwife , Earth to earth: Gravedigger , The devil's coachman: Crematorium operator , The hopeful dead: Cryonics institute.

Hey, water! (Holiday House, 2019)
"As the girl discovers water in nature, in weather, in her home, and even inside her own body, water comes to life, and kids will find excitement and joy in water and its many forms"--

The lost family: how DNA testing is upending who we are (Abrams, ABRAMS, Inc., Blackstone Publishing, 2020)
"You swab your cheek or spit in a vial, then send it away to a lab somewhere. Weeks later you get a report that might tell you where your ancestors came from or if you carry certain genetic risks. Or the report could reveal long-buried family secrets and upend your entire sense of identity. Soon a lark becomes an obsession, a relentless drive to find answers to questions at the core of your being, like "Who am I?" and "Where did I come from?" Welcome to the age of home genetic testing. In The Lost Family, journalist Libby Copeland investigates what happens when we embark on a vast social experiment with little understanding of the ramifications. She explores the culture of genealogy buffs, the science of DNA, and the business of companies like Ancestry and 23andMe, all while tracing the story of one woman, her unusual results, and a relentless methodical drive for answers that becomes a thoroughly modern genetic detective story. Gripping and masterfully told, The Lost Family is a spectacular book on a big, timely subject" -- Goodreads.com.

Inky's amazing escape: how a very smart octopus found his way home (Rhode Island Children's Book Award Winner 2020, ,, 2018)
"The story of how in April 2016, Inky the octopus escaped from the New Zealand aquarium and became an international sensation."--

Good prose: the art of nonfiction (Tantor Media, Inc., Random House Publishing Group, Random House, 2017)
"Good Prose" is an inspiring book about writing--about the creation of good prose--and the record of a warm and productive literary friendship.